General View of the Trinidad Marine Club - (:unkn) unknown (My University, 2009)
A view of Trinidad Marine Club, Staubles Bay, Chaguaramas surrounded on three sides by coconut trees and the ocean on the other. The main building has an open veranda overlooking a swimming pool.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Clubs--Trinidad and Tobago; Swimming pools--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Chaguaramas; Trinidad Marine Club, The (Chaguaramas)